Evaluating the Impact of Opium Poppy Toxicity on Pediatric Patients: Clinical, Laboratory, and Outcome Analysis - Obaid ur Rehman, Younas Khan, Mohammad Haneef, Muhammad Zubair, Noor Ul Saba Khattak, Mohammad Munib, Sadaf Sabah, Shabir Ahmad Orakzai, (Pakistan Journal of Medical & Health Sciences, 2024)
Traditionally, the opium poppy plant, Papaver somniferum L., has been used for a variety of therapeutic uses, such as pain treatment and cough suppression. Hippocrates once described the herb as hypnotic, cathartic, and styptic. The current study was conducted at the Tertiary Care Hospitals in Peshawar, KPK, Pakistan, from August 2022 to August 2023. It examined the clinical and laboratory profiles of newborns and children admitted to a tertiary care hospital with poppy intake and compared the profiles between those who survived and those who died. All infants and kids who showed up for the research period exhibiting meiosis, respiratory depression, and decreased consciousness all indications of opium poppy intoxication as well as a verified history of poppy administration at home, were included in the study. There were admittedly 65 cases of opium poppy intoxication. The patients' ages varied from one month to twenty-three months, with an average age of 7.22 ± 5.43 months. 35 (53.85%) of these infants and children died, while 30 (46.15%) survived (p<0.001). Those who survived had a considerably shorter period from poppy intake to hospital admission (6.0 ± 2.56 hours versus 12.47 ± 4.14 hours, p<0.001) than those who died. Children who were administered poppy powder mixed with water had a considerably higher mortality rate 13 out of 17 cases (76.47%) resulted in death (p<0.001). There was a strong correlation between increased mortality and low respiratory rate, decreased oxygen saturation, aspiration pneumonia, apneic episodes, cyanosis, and leukocytosis >15,000/mm³. For newborns, opium poppy poses a serious risk because it can cause a coma, impair breathing, and even be lethal. The selling of poppies in shops and supermarkets must be outlawed, and public education is essential to ending this destructive activity. Keywords: Opium Poppy, Toxicity, Infants and Children, Meiosis, Respiratory Depression